5 - The Role of Trust as an Informal Institution in the Informal Sector in Africa - Odera, Levy Charles (Africa Development, 2021)
The study analyses an unexplored issue of how trust, framed as an informal institution, plays an important role in business operations in the informal sector by filling the vacuum left by the lack of formal institutions. It brings together ‘snapshots’ from other studies that show how trust plays a role in the informal sector. In the author’s approach, trust is framed under informal institutions. Under this framework the author presents a larger picture of the significant role of trust as an informal institution used in the business operations within the informal sector in Africa. In the study, trust is analysed from two main dimensions, namely: Social Networks Dimension and Business Cooperation Dimension. The study is divided into four main sections: the first section presents an overview of the informal sector; the second section analyses the Social Networks Dimension, the third section analyses the Business Cooperation Dimension, and the fourth part concludes by hypothesizing a causal relationship between trust, the two dimensions, and socio-economic development.